The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2460/ajvr.81.9.732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slice thickness on computed tomographic perfusion analysis of the pancreas in healthy dogs

Abstract: OBJECTIVE To evaluate the effect of slice thickness on CT perfusion analysis of the pancreas in healthy dogs. ANIMALS 12 healthy Beagles. PROCEDURES After precontrast CT scans, CT perfusion scans of the pancreatic body were performed every second for 30 seconds by sequential CT scanning after injection of contrast medium (iohexol; 300 mg of 1/kg) at a rate of 3 mL/s. Each dog underwent CT perfusion scans twice in a crossover-design study with 2 different slice thicknesses (2.4 and 4.8 mm). Computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Dynamic contrast‐enhanced computed tomography has been used in dogs, and several proof‐of‐principle studies have assessed normal tissues and tumors, and compared DCECT to 18F‐fluorodeoxyglucose positron emission tomography‐computed tomography. 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Two studies specifically reported DCECT in nasal tumors but did not find correlation with histogenesis or survival. 33 , 39 Our objectives were (a) to assess baseline perfusion parameters in dogs with nasal tumors based on histopathological type, (b) to characterize changes in perfusion parameters with changes in tumor volume after the start of RT, and (c) to evaluate if a correlation existed of either objective 1 or objective 2 with survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic contrast‐enhanced computed tomography has been used in dogs, and several proof‐of‐principle studies have assessed normal tissues and tumors, and compared DCECT to 18F‐fluorodeoxyglucose positron emission tomography‐computed tomography. 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 Two studies specifically reported DCECT in nasal tumors but did not find correlation with histogenesis or survival. 33 , 39 Our objectives were (a) to assess baseline perfusion parameters in dogs with nasal tumors based on histopathological type, (b) to characterize changes in perfusion parameters with changes in tumor volume after the start of RT, and (c) to evaluate if a correlation existed of either objective 1 or objective 2 with survival.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic contrast‐enhanced computed tomography has been used in dogs, and several proof‐of‐principle studies have assessed normal tissues and tumors, and compared DCECT to 18F‐fluorodeoxyglucose positron emission tomography‐computed tomography 26‐42 . Two studies specifically reported DCECT in nasal tumors but did not find correlation with histogenesis or survival 33,39 .…”
Section: Introductionmentioning
confidence: 99%